Traditional Medicine in Filipino Patients’ Therapeutic Itineraries - Lasco, Gideon (Archīum Ateneo, 2025)
In medical anthropology and public health, there has been a longstanding scholarly focus on the different forms of traditional medicine (TM) how they can collaborate with biomedical health systems and how people actually embrace both as part of their medical pluralism. However, less attention has been paid on the temporal relationships between TM and biomedicine within individual patient pathways. This paper charts the roles that TM play within the therapeutic itineraries of Filipino patients. In unearthing these connections, we draw from an extensive, multi-sited qualitative study featuring over 30 FGDs involving various demographics and geographic settings in the Philippines. We find that TM figures in people's therapeutic itineraries before, alongside, and after treatment and that even before consulting traditional healers, people engage in traditional practices on their own. Some diseases are perceived as not warranting biomedical help, while others are seen as deserving a ‘trial’ of TM before biomedical consult there are also conditions that are seen to be benefit from both - and traditional medicine is also considered a ‘last resort’ if biomedical treatments fail. By identifying the ways in which the temporalities of TM interact with biomedicine, our findings can inform health communications and other public health efforts, while providing a contemporary picture of TM in the country.